Renal transplantation in small children: a comparison between surgical procedures - Adams, Judith; Güdemann, C.; Tönshoff, Burkhard; Mehls, Otto; Wiesel, Manfred (European urology, 2001)
Renal transplantation is the therapy of choice for patients with end-stage renal failure. From the surgical point of view, small children remain a challenging patient group.